2004
DOI: 10.21236/ada443787
|View full text |Cite
|
Sign up to set email alerts
|

Material Surface Design to Counter Electromagnetic Interrogation of Targets

Abstract: Utilization of controllable ferroelectric and ferromagnetic layers coating a conducting object to provide an attenuation capability against electromagnetic interrogation is discussed. The problem is formulated as a differential game and/or a robust optimization. The scattered field due to interrogation can be attenuated with the assumption of an uncertainty in the interrogation wave numbers. The controllable layer composed of ferromagnetic and ferroelectric materials [9, 10] is incorporated in a mathematical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…GROVE, K. ITO and J.A. TOIVANEN 291 fields from an object such as an airfoil or missile and can be computed in one of several ways [8,9]. The simplest is the reflection coefficient based on a simple planar geometry (e.g., see Figure 1) using Fresnel's formula for a perfectly conducting half plane which has a coating layer of thickness d with dielectric permittivity and magnetic permeability μ.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…GROVE, K. ITO and J.A. TOIVANEN 291 fields from an object such as an airfoil or missile and can be computed in one of several ways [8,9]. The simplest is the reflection coefficient based on a simple planar geometry (e.g., see Figure 1) using Fresnel's formula for a perfectly conducting half plane which has a coating layer of thickness d with dielectric permittivity and magnetic permeability μ.…”
Section: Problem Formulationmentioning
confidence: 99%
“…In [8] the authors demonstrated that it is possible to design ferroelectric materials with appropriate dielectric permittivity and magnetic permeability to significantly attenuate reflections of electromagnetic interrogation signals from highly #688/06. Received: 01/IX/06.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preconditioning of discretized scattering problems in layered media without an object has been considered in [8,9,24,25,28], for example, and with an object in [17]. The domain decomposition method introduced in [13] and employed in [3] for computing electromagnetic scattering by coated objects is based on a similar approach to the one considered in here. In [13] the electromagnetic scatterer is perfectly conducting with a dielectric coating layer which would corresponds to a sound-soft acoustic scatterer with a coating layer having different density and speed of sound.…”
Section: Introductionmentioning
confidence: 99%
“…We present numerical results on scattering by an aluminum disk with one feet diameter and the center at (0 m, −0.2524 m). The density of aluminum is 2700 kg/m3 and its compressional speed and shear speed are c c = 6568 m/s and c s = 3149 m/s, respectively. The surface of the sediment is defined by x 2 = f (x 1 ) = (0.0368 m) cos(360 • x 1 /(0.75 m)).…”
mentioning
confidence: 99%